2012
DOI: 10.1038/pr.2012.74
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic–ischemic retinal injury in rat pups

Abstract: Background: Visual loss associated with brain damage, especially hypoxic-ischemic (hI) encephalopathy, is the most common cause of visual impairment in children in developed countries. We hypothesized that hI insults can cause long-term damage in immature eyes. Methods: In postnatal day 7 rat pups, hI was induced by unilateral common carotid artery ligation followed by hypoxia. Retina damage was assessed by electroretinography (eRG) and cell counting. Neuronal injury and astrogliosis were evaluated by terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 28 publications
2
38
2
1
Order By: Relevance
“…The extent of retinal damage was quantified by two independent observers, in two nonoverlapping visual fields (250 3 250 lm) within central areas (100 lm from the optic disc). 8 …”
Section: Assessment Of Retinal Injurymentioning
confidence: 99%
See 4 more Smart Citations
“…The extent of retinal damage was quantified by two independent observers, in two nonoverlapping visual fields (250 3 250 lm) within central areas (100 lm from the optic disc). 8 …”
Section: Assessment Of Retinal Injurymentioning
confidence: 99%
“…8 Therefore, future therapeutic strategies for treating HI insults should take into account the retina in addition to the brain. Furthermore, it has been shown that BDNF enhances RGC survival and function when injected both to the eyes and central visual pathway than only to the eyes.…”
Section: / Chx10mentioning
confidence: 99%
See 3 more Smart Citations